Effects of two types of energy restriction on methylation levels of adiponectin receptor 1 and leptin receptor overlapping transcript in a mouse mammary tumour virus-transforming growth factor-α breast cancer mouse model. Issue 1 (14th January 2021) - Cicekdal, M. B.; Kazan, B. T.; Tuna, B. G.; Ozorhan, U.; Ekici, I. D.; Zhu, F.; Suakar, O.; Kuskucu, A.; Bayrak, O. F.; Arcaro, K.; Cleary, M. P.; Dogan, S.; et al.
Abstract: The role of adiponectin and leptin signalling pathways has been suggested to play important roles in the protective effects of energy restriction (ER) on mammary tumour (MT) development. To study the effects of ER on the methylation levels in adiponectin receptor 1 ( AdipoR1 ) and leptin receptor overlapping transcript ( Leprot ) genes using the pyrosequencing method in mammary fat pad tissue, mouse mammary tumour virus-transforming growth factor- α (MMTV-TGF- α ) female mice were randomly assigned to ad libitum (AL), chronic ER (CER, 15 % ER) or intermittent ER (3 weeks AL and 1 week 60 % ER in cyclic periods) groups at 10 weeks of age until 82 weeks of age. The methylation levels of AdipoR1 in the CER group were higher than those in the AL group at week 49/50 ( P < 0·05), while the levels of methylation for AdipoR1 and Leprot genes were similar among the other groups. Also, the methylation levels at CpG2 and CpG3 regions of the promoter region of the AdipoR1 gene in the CER group were three times higher ( P < 0·05), while CpG1 island of Leprot methylation was significantly lower compared with the other groups ( P < 0·05). Adiponectin and leptin gene expression levels were consistent with the methylation levels. We also observed a change with ageing in methylation levels of these genes. These results indicate that different types of ER modify methylation levels of AdipoR1 and Leprot in different ways and CER had a more significant effect on methylation levels of both genes. Epigenetic regulation of these genes may play important roles in the preventive effects of ER against MT development and ageing processes.